The Effectiveness of Counseling Using Phantom Media and Puzzle Games on the Improve Dental Health Knowledge of Elementary School Children in Kupang City - Pay, Mery Novaria; Marlina A.Pinat, Leny; Ngadilah, Christina; O.Nubatonis, Melkisedek (Jurnal Kesehatan Gigi, 2025)
Health promotion in elementary school age is an ideal time to train motor skills and improve children's cognition. The success of dental health promotion is influenced by the presence of interesting game media used by dental and oral therapists as the main competency in promotive efforts. Health workers are expected to be able to use media appropriately, be able to design and produce game media. This study aims to determine the effectiveness of the use of promotional media by dental and oral therapists in Kupang City in improving elementary school children's knowledge about dental health. The research method used in the study was Quasi Experiment with a two group pre-test and post-test design. Sampling was carried out using multistage cluster random sampling with a sample size of 220 children in 11 elementary schools fostered by UKGS from 11 health centers throughout Kupang City. The sample was divided into 2 groups, namely 110 children who used media provided by dental and oral therapists as the control group and 110 children who used puzzle game media provided by researchers as the treatment group. The knowledge variable was measured using a questionnaire, most of the data were not normally distributed so data analysis was carried out using Mann-Whitney. The results of the analysis of differences using the Mann-Whitney Test at pre-post 2 showed a significant increase in knowledge in both groups. The mean value in the control group was 184.72 lower than the treatment group of 256.28. This study concluded that puzzle game media is more effective in providing dental and oral health education to elementary school children compared to promotional media used by dental and oral therapists.